The contribution of Papyrus Ashmolean Museum 1945.96 (Adoption Papyrus) to our understanding of the ancient egyptian “testamentary disposition” and succession law - van Blerk, Nico (Journal for semitics, 2020)
This article will focus on the importance of the New Kingdom Papyrus Ashmolean Museum 1945.96 (Adoption Papyrus). The research question is whether this papyrus assists us in a better understanding of the ancient Egyptian testamentary disposition. The aim is to identify and discuss concepts and elements pertaining to succession law in general, but in particular testamentary dispositions. A problem when studying any ancient text is to keep in mind that one can never enforce modern concepts onto these ancient texts. However, these ancient texts might contain building blocks of later concepts; in particular, the Adoption Papyrus may give us valuable information regarding these early concepts and elements of succession law and in the process indicate that the building blocks of succession law are much older than Roman law. The methodology used is a textual approach analysing the Adoption Papyrus in order to attempt identifying legal concepts and elements of succession law. With my background as lawyer and Egyptologist, it appears to me that there are several identifiable elements and concepts of testamentary dispositions and succession law evident in the Adoption Papyrus. With my multi-disciplinary approach to this study, I endeavour to indicate that the first building blocks of the testamentary disposition and succession law can be found in these ancient New Kingdom texts, long before Roman law was developed.